Piłka nożna, amerykański izolacjonizm i paradoksy globalizacji - Melosik, Zbyszko (Studia Edukacyjne, 2020)
The article is devoted to analyzing the North American attitude towards soccer. American arguments against soccer are presented against the background of prevailing tendencies of world globalization. Also, the essence of soccer is confronted with the American version of masculinity, symbolized by aggressive American football.